Group based learning among caregivers: assessing mothers' knowledge before and after an early childhood intervention in rural Guatemala. (June 2019) - Domek, Gretchen J.; Macdonald, Brittney; Cooper, Catherine; Cunningham, Maureen; Abdel-Maksoud, Madiha; Berman, Stephen
Background: The first three years of a child's life are a critical period for brain growth and development. Caregiver interventions during this period that improve early childhood health and development have the potential to enhance a child's physical, mental, and social well-being. Methods: This was a pretest/posttest quasi experimental program evaluation. Early childhood education materials were adapted to create two separate interventions consisting of 30-page interactive flipchart talks to educate mothers on health and development topics relevant to 0–6 and 6–12 month old children. Three community health workers performed the talks with groups of 5–8 mothers. Short learning assessments were given individually to each mother pre-intervention (pretest), immediately post-intervention (posttest 1), and two weeks post-intervention (posttest 2). Demographic surveys and focus group discussions were conducted with all participants. Results: Mothers ( n = 77) had an average age of 33.6 years and had an average of 3.6 living children. Most of the mothers (71%) had received some primary education, but 23% had received no formal schooling. For the 0–6 months flipchart learning assessment ( n = 38), the mean pretest score was 77% correct. The mean posttest 1 score improved to 87% ( p < 0.0001), and the mean posttest 2 score improved further from the mean posttest 1 score to 90% ( p = 0.01). For the 6–12 months flipchart learning assessment ( n = 39), the mean pretest score was 78%. The mean posttest 1 score improved to 89% ( p < 0.0001), and the mean posttest 2 score improved further from the mean posttest 1 score to 92% ( p = 0.03). Conclusions: Mothers in an impoverished region of southwestern Guatemala significantly increased their knowledge about child health topics following a short interactive group talk. Mothers further increased their knowledge two weeks after the intervention, without specific re-exposure to the intervention materials, suggesting assimilation and informal reinforcement through group based learning with other mothers in their community.